Peran Modal Sosial Sebagai Moderator Dampak Green Marketing dan Digital Flatform Capability terhadap Kinerja Pemasaran pada Womenpreneur Sektor Agri-Food - Andardinata, Ady; Arman Kamal; Hardiyanti T (Al-Buhuts, 2024)
The potential of MSMEs in the agri-food sector is very high because it is an agricultural region in Indonesia. The majority of MSME workers in the agri-food sector are women. Gender marginalization often occurs where women are marginalized due to social stigma. Womenpreneurs are often looked down upon and find it difficult to compete. This study aims to test the moderating role of social capital on the influence of green marketing and digital platform capability on marketing performance in womenpreneurs in the agri-food sector in Makassar City. This study uses a quantitative approach with partial least squares structural equation modeling (PLS-SEM) analysis. The object of the study was womenpreneurs in the agri-food sector with a total data of 210 womenpreneurs. The results showed that green marketing and digital platform capability had an effect on marketing performance. Social capital plays a role in moderating the relationship between green marketing and marketing performance, but does not moderate the relationship between digital platform capability and marketing performance.